A Possible Therapeutic Application of the Selective Inhibitor of Urate Transporter 1, Dotinurad, for Metabolic Syndrome, Chronic Kidney Disease, and Cardiovascular Disease - Hidekatsu Yanai; Hiroki Adachi; Mariko Hakoshima; Sakura Iida; Hisayuki Katsuyama (Cells, 2024)
The reabsorption of uric acid (UA) is mainly mediated by urate transporter 1 (URAT1) and glucose transporter 9 (GLUT9) in the kidneys. Dotinurad inhibits URAT1 but does not inhibit other UA transporters, such as GLUT9, ATP-binding cassette transporter G2 (ABCG2), and organic anion transporter 1/3 (OAT1/3). We found that dotinurad ameliorated the metabolic parameters and renal function in hyperuricemic patients. We consider the significance of the highly selective inhibition of URAT1 by dotinurad for metabolic syndrome, chronic kidney disease (CKD), and cardiovascular disease (CVD). The selective inhibition of URAT1 by dotinurad increases urinary UA in the proximal tubules, and this un-reabsorbed UA may compete with urinary glucose for GLUT9, reducing glucose reabsorption. The inhibition by dotinurad of UA entry via URAT1 into the liver and adipose tissues increased energy expenditure and decreased lipid synthesis and inflammation in rats. Such effects may improve metabolic parameters. CKD patients accumulate uremic toxins, including indoxyl sulfate (IS), in the body. ABCG2 regulates the renal and intestinal excretion of IS, which strongly affects CKD. OAT1/3 inhibitors suppress IS uptake into the kidneys, thereby increasing plasma IS, which produces oxidative stress and induces vascular endothelial dysfunction in CKD patients. The highly selective inhibition of URAT1 by dotinurad may be beneficial for metabolic syndrome, CKD, and CVD.